(3CSGdjH GdaYGdjI dRjGOI GdeHjYGJ (B/s - (3hGWShf, fjds; (3gQSJ, SJja s ((3GdbGgQI(B: s (3OGQ GdaGQhb ddfTQ hGdJhRjY(B, s, 2001)
(3GdCSGdjH GdaYGdI dRjGOI GdeHjYGJ(B- (3GdWQjbI GdLjOI dYQV GdSdY gj GdWQjbI GdeKdi ddfLGM(B- (3HYV GdCacGQ GdYedjI GddGReI YfO GdJYGed eY GdYedGA(B- (3GdJaGhV cCMO egGQGJ GdHjY(B- (3cja JdHj EMJjGLGJ GdYedGA?(B- (3cjajI RjGOI aGYdjI JcfhdhLjG GdEJUGdGJ(B- (3cjajI GdJYGed eY cGaI GdGehQ GdeGOjI(B- (3GdMjGI GdUMjI(B.s
Keywords: (3COGQI GdeHjYGJs; (3GdeHjYGJs